Preinstalled functionality as a service - Dhebar, Anirudh (Business horizons, 2023)
During the summer of 2022, carmaker BMW introduced postpurchase, subscription-based “functions on demand,” and the online response was furious. Having purchased a car with functionalities preinstalled, consumers expect to use the functionalities as and when they wish and without additional charges. BMW was changing this norm and so became the object of derision. We live in an age of “x as a service” and amid a subscription economy, and electronics and software are making their way into all kinds of products—products that are connected to the internet at all times, controlled through apps on mobile devices, and subject to the product maker’s “off” and “on” instructions. “Preinstalled functionality as a service” is now technologically possible, the economic pull of recurring revenue is enticing, and perhaps BMW should not be blamed: We are possibly at the threshold of a new way of thinking about durable products and their preinstalled bundle of functions. This article introduces the concept of preinstalled functionality as a service and characterizes how this business-model innovation changes the concepts of durable products, product lines, after-purchase add-ons, and functionality usage rights. I conclude by examining whether and how the innovation may be implemented.